Within, Without, Withinwards: The Circulation of Sound in Shakespeare’s Theater - Bruce R. Smith (Sillages Critiques)
This article considers air as a medium and explores the analogy between inside and outside in the production of vocal sound and in the circulation of sound within the Globe. I propose to survey the three containers that shaped the air that circulated in Shakespeare’s original theater: the tiring house, the amphitheater, and the human body.